Design and simulation of offshore crane structure with capacity of 400 ton - Freddy Marpaung; Harry Purnama; I Nyoman Artana; Nani Kurniawati; Dian Samodrawati; Tri Surawan; Harini Agusta (Politeknik Negeri Lhokseumawe, 2024)
Offshore cranes are transport machines which are used to lift a heavy load to other places. The weight and strength of a crane are crucial parameters that must be considered during the design stage. There are many ways to optimize these aspects, such as suitable material selection and virtual simulation assistance using ANSYS software. The main goal of this study is to design and develop a structurally stable crane on the ship deck. This crane is modeled using CATIA software and analyzed using ANSYS software to obtain stress and displacement distribution on the crane structure. Maximum load is applied for four different elevation angles, namely (30°, 43°, 60°, and 80°). From the static structural simulation, the highest stress is obtained when the elevation angle of 30° is about 1030 MPa and deformation is 461.24 mm. The minimum fatigue life of the offshore crane at a luffing angle of 43° is 659.14 cycles.